Phosphate Binders and Targets Over Decades: Do We have it Right Now?. Issue 2 (8th January 2017) - Marcuccilli, Morgan; Chonchol, Michel; Jovanovich, Anna
Abstract: In advanced renal disease, the kidney is unable to maintain phosphate balance due to decreased urinary excretion as well as the imbalance of the bone metabolic axis. It is well established that hyperphosphatemia is associated with increased cardiovascular events and mortality in patients with chronic kidney disease (CKD). However, there are no randomized controlled trials that demonstrate a clear benefit on hard outcomes in lowering serum phosphate levels to recommended targets in the CKD or dialysis population. In addition, while calcium‐based phosphate binders have traditionally been the standard of care in the treatment of hyperphosphatemia, data regarding the increased risk of vascular mineralization continues to emerge. Clinicians continue to search for new phosphate‐lowering therapies as well as investigate novel nutritional perspectives. The Kidney Disease: Improving Global Outcomes is currently revising the guidelines on phosphate goals in CKD. This review will outline the history of phosphate targets and phosphate binders, and explore innovative phosphate‐lowering therapies. Based on current data, clinicians moving forward should continue to treat end‐stage renal disease patients with hyperphosphatemia based on individual risk factors for vascular mineralization.